Longevity of Anterior Composite Restorations in a General Dental Practice-Based Network. (September 2017) - Collares, K.; Opdam, N.J.M.; Laske, M.; Bronkhorst, E.M.; Demarco, F.F.; Correa, M.B.; Huysmans, M.C.D.N.J.M.
This practice-based study investigated the performance of a large set of anterior composite restorations placed by a group of 24 general practices. Based on data from electronic patient files, the longevity of 72, 196 composite restorations was analyzed, as placed in 29, 855 patients by 47 general dental practitioners between 1996 and 2011. Annual failure rates (AFRs) were calculated, and variables associated with failure were assessed by multivariate Cox regression analysis with shared frailty for 2 age groups (5 to 24 y and ≥25 y). The observation time of restorations varied from 2 wk to 13 y, with a mean of 4.8 y, resulting in a mean AFR of 4.6% (95% confidence interval [95% CI], 4.5% to 4.6%) at 5 y. Among dentists, a relevant variation in clinical performance of restorations was observed, with an AFR between 2% and 11%. The risk for restoration failure increased in individuals up to 12 y old, having a 17% higher risk for failure when compared with the age group of 18 to 25 y (hazard ratio, 1.17; 95% CI, 1.03 to 1.34), and for the age group >65 y, having a 81% higher risk for failure when compared with 25 to 35 y (hazard ratio, 1.81; 95% CI, 1.66 to 1.98). In both multivariate models, there was a difference in longevity of restorations for different teeth in the arch, with fillings in central incisors being the most prone to failure and replacement. It was concluded that anterior composite restorations placed by general dental practitioners showed an adequate clinical performance, with a relevant difference in outcome among operators.